Influencia del proceso de comunicación interpersonal entre las personas con discapacidad y los facilitadores del centro diurno de desarrollo integral para personas con discapacidad-Loja, período diciembre 2016 - abril 2017 - Franzcine Beatriz, Masache Novillo (2017)
The influence of the interpersonal communication process among disable people and facilitators of the diurnal center of integral development for people with disabilities-Loja period December 2016-april 2017. This was the thematic and general objective for the investigation in the present work. Since the methodological point of view, it was delimited the universe investigated, this was integrated by the coordinator of the diurnal center of integral development for people with disabilities, three facilitators of the center and one parent of family, in which it was applied a guide of interview previously structured, thirty people with disability that assist to the center, with them was convenient the used of observation sheets and focal groups; the total people in which we applied the techniques and instruments were thirty five that gives a reliable result to obtain the required information for this work. The results obtained shows that in the diurnal center of integral development for people with disabilities, it promotes the interpersonal communication in a limited way among people with disabilities and the facilitator; and the learners that get into the center in a fifty percent have problems at the time of incorporating skills from the contents that the teacher impart in his classes.it is concluded that the limited promotion of communication among facilitators and learners of the center of integral development for people with disabilities preclude the improvement of the skills related to the communication for the people who attend to the same, in which gives a negative influence in the inclusion of people with disability to the society, to this effect, it is advisable for the authorities of the diurnal center of integral development for people with disabilities, to make activities that promotes the interpersonal communication among facilitators and people with disabilities.